The Present Situation and Countermeasures of English Education and Curriculum Management in Xiuwu Rural Primary Schools under the background of China’s internationalization and the Belt and Road Initiative - Nie, Yangmei; Chiwpreecha, Dr.Kesinee (Journal of Dhamma for Life, 2024)
The aims of this article were to present situation, problems and scountermeasures of English Education and Curriculum Management in Xiuwu Rural Primary Schools under the background of China’s internationalization and the Belt and Road Initiative. According to the field survey, network survey, network data, combined with the increasing number of Chinese students going international and the background of China’s "One Belt and One Road" policy, it is found that Xiuwu Rural Primary School in Jiaozuo City, Henan Province, does not pay attention to English teacher allocation, English education and teaching professionalism, English teaching knowledge application, students’ English quality development and curriculum management. This results in the low quality education of students. We should pay attention to the optimization of education management in rural schools. This paper will make a summary of the problems of English education and management in the region and summarize the countermeasures, hoping to have a certain good impact on English teaching in the country and other areas, and attract the attention of schools.